STUDIES ON PHYSICAL PROPERTIES OF CERVICAL MUCUS OF REPEAT BREEDING CROSSBRED COWS - ZAMAN, MALIK IMRANUL; SHARMA, UTSAV; KUMAR, SUDHIR; KUMAR, SHARAD (The Indian Journal of Animal Reproduction, 2023)
The examination of physical properties of cervical mucus in majority of the repeat breeding cows showedthat the colour was turbid (64.44%), consistency was thick (84.44%), elasticity was elastic (62.22%) and fernpattern was typical (60.00% ). The pH value of cervical mucus in repeat breeding (7 .95 ± 0.096) cows was significantly(p
Keywords: Physical property; Cervical mucus; Repeat breeding cow